Description of New and Amended Clades of the Genus Photobacterium. - Labella Vera, Alejandro Manuel; Castro-López, María Dolores; Manchado, Manuel; Borrego-García, Juan José (MDPI, 2018)
Phylogenetic relationships between species in the genus Photobacterium have been poorly studied despite pathogenic and ecological relevance of some of its members. This is the first phylogenetic study that includes new species of Photobacterium (validated or not) that have not been included in any of the previously described clades, using 16S rRNA sequences and multilocus sequence analysis (MLSA) in concatenated sequences of gyrB, gapA, topA, ftsZ and mreB housekeeping genes. Sequence analysis has been implemented using Maximum-parsimony (MP), Neighbour-joining (NJ) and Maximum likelihood (ML) treeing methods and the predicted evolutionary relationship between the Photobacterium clades was established on the basis of bootstrap values of >75% for 16S rRNA sequences and MLSA. We have grouped 22 species of the genus Photobacterium into the following 5 clades: Phosphoreum (comprises P. aquimaris, “P. carnosum,” P. iliopiscarium, P. kishitanii, P. phosphoreum, “P. piscicola” and “P. toruni”); clade Profundum (composed of P. aestuarii, P. alginatilyticum, P. frigidiphilum, P. indicum, P. jeanii, P. lipolyticum, “P. marinum,” and P. profundum); clade Damselae (two subspecies of P. damselae, damselae and piscicida); and two new clades: clade Ganghwense (includes P. aphoticum, P. aquae, P. galatheae, P. ganghwense, P. halotolerans, P. panuliri and P. proteolyticum); and clade Leiognathi (composed by P. angustum, P. leiognathi subsp. leiognathi and “P. leiognathi subsp. mandapamensis”). Two additional clades, Rosenbergii and Swingsii, were formed using a phylogenetic method based on 16S rRNA gene, although they are not confirmed by any MLSA methods. Only P. aplysiae could not be included in none of the established clade, constituting an orphan clade.
Keywords: Bacterias gram negativas; Photobacterium specis; Phylogenetic study; Clades